Evaluation of BAM (butorphanol–azaperone–medetomidine) in captive African lion (Panthera leo) immobilization. (July 2017) - Semjonov, Aleksandr; Andrianov, Vladimir; Raath, Jacobus P.; Orro, Toomas; Venter, Derik; Laubscher, Liesel; Pfitzer, Silke
Abstract: Objective: The combination of butorphanol, azaperone and medetomidine (BAM) with subsequent antagonism by naltrexone–yohimbine or naltrexone–atipamezole was evaluated for reversible immobilization of captive African lions ( Panthea leo ). Study design: Prospective, clinical trial. Animals: Twenty lions, 11 males and nine females, weighing 38–284 kg were immobilized in South Africa. Methods: The BAM volume dose rate administered was 0.005–0.008 mL kg −1 (0.6 mL 100 kg −1 ). Physiologic variables were recorded every 5 minutes. Four arterial blood samples were collected from all animals at 20, 30, 40 and 50 minutes after immobilization for analysis of blood-gases and acid-base status. Results: The actual doses administered were as follows: butorphanol, 0.18 ± 0.03 mg kg −1 ; azaperone, 0.07 ± 0.01 mg kg −1 ; and medetomidine, 0.07 ± 0.01 mg kg −1 . The inductions were calm and smooth, and induction time ranged from 4 to 10 minutes (7 ± 2 minutes). The amount of time needed to work with each lion was 70 minutes, and no additional drug doses were needed. Heart rate (40 ± 8 beats minute −1 ) and respiratory frequency (15 ± 4 breaths minute −1 ) were stable throughout immobilization. The mean arterial blood pressure of all animals was stable but elevated (142 ± 16 mmHg). The rectal temperature slightly increased over time but remained within acceptable range. The recovery time was significantly shorter when using naltrexone and atipamezole (9 ± 1 minutes) compared to using naltrexone and yohimbine (22 ± 7 minutes). Conclusion and clinical relevance: The BAM combination proved to be reliable for general veterinary anaesthesia in lions. During anaesthesia, minor veterinary procedures such a blood collection, intubation, vaccination and collaring could safely be performed with no additional dosing required.